Pharmacist Perceptions of the use of IT within the Retail Pharmacy Sector in Two Regions in Trinidad A Retrospective Study - Maharaj, Sandeep (International Journal of Pharmaceutical & Biological Archive, 2012)
Pharmacist Perceptions of the use of IT within the Retail Pharmacy Sector in Two Regions in Trinidad A Retrospective Study